Dynamics Management Analysis of the Baitul Maal Mosque and the Relationship With the People Empowerment (Study of the Baitul Maal Mosque in Surakarta, 2016) - Danurdara, Paksi; Daerobi, Akhmad; Pratama, Yogi Pasca (Jurnal Ilmu Ekonomi Terapan, 2017)
This research aims to measure the dynamics level of the Baitul Maal Masjid group management and its correlation with the empowerment of the people in Surakarta's Mosque. Subjects in this research took five people in each Baitul Maal Masjid which was considered informative, using the purposive sampling technique. The results showed that the dynamics level of the Baitul Maal Masjid management group in Surakarta City was included in the dynamic category. The dynamism of the group is scored through the 9 elements: group goal, group structure, task function, group building and maintenance, group cohesiveness, group atmosphere, group pressure, group effectiveness, and hidden agenda. The most dynamic group of Baitul Maal Masjid managers is Baiturrahman mosque with a 396 dynamics score, then Nurhasanah with a score 394.4, followed by Muttaqin-Al-Hakim with a score 393.6, and Hidayatullah with score 383.2. The dynamism of the group is equivalent to the aims of the Baitul Maal Masjid group. The mosque empowers the mosque and empowers the people. The more dynamic of Baitul Maal Masjid group, then the purpose of the Baitul Maal Masjid group more easily to be carried out optimally. Implementation of Baitul Maal Mosque requires the role of funds collected and funds channelled by each mosque to realize the empowerment of the people.